Modeling Vestibular Compensation: Neural Plasticity Upon Thalamic Lesion - Reuss, Stefan; Siebrecht, Elena; Stier, Ulla; Buchholz, Hans-Georg; Bausbacher, Nicole; Schabbach, Nadine; Kronfeld, Andrea; Dieterich, Marianne; Schreckenberger, Mathias (Frontiers in Neurology, 2020)
The present study in rats was conducted to identify brain regions affected by the interruption of vestibular transmission and to explore selected aspects of their functional connections. We analyzed, by positron emission tomography (PET), the regional cerebral glucose metabolism (rCGM) of cortical and subcortical cerebral regions processing vestibular signals after an experimental lesion of the left laterodorsal thalamic nucleus, a relay station for vestibular input en route to the cortical circuitry. PET scans upon galvanic vestibular stimulation (GVS) were conducted in each animal prior to lesion and at post-lesion days (PLD) 1, 3, 7 and 20, and voxel-wise statistical analysis of rCGM at each PLD compared to pre-lesion status were performed. After lesion, augmented metabolic activation by GVS was detected in cerebellum, mainly contralateral, and in contralateral subcortical structures such as superior colliculus, while diminished activation was observed in ipsilateral visual, entorhinal and somatosensory cortices, indicating compensatory processes in the non-affected sensory systems of the unlesioned side. The changes in rCGM observed after lesion resembled alterations observed in patients suffering from unilateral thalamic infarction and may be interpreted as brain plasticity mechanisms associated with vestibular compensation and substitution. The second set of experiments aimed at the connections between cortical and subcortical vestibular regions and their neurotransmitter systems. Neuronal tracers were injected in regions processing vestibular and somatosensory information. Injections into the anterior cingulate cortex (ACC) or the primary somatosensory cortex (S1) retrogradely labeled neuronal somata in ventral posteromedial (VPM), posterolateral (VPL), ventrolateral (VL), posterior (Po), and laterodorsal nucleus, dorsomedial part (LDDM), locus coeruleus and contralateral S1 area. Injections into the parafascicular nucleus (PaF), VPM/VPL or LDDM anterogradely labeled terminal fields in S1, ACC, insular cortex, hippocampal CA1 region and amygdala. Immunohistochemistry showed tracer-labeled terminal fields contacting cortical neurons expressing the µ-opioid receptor. Antibodies to tyrosine hydroxylase, serotonin, substance P, or neuronal nitric oxide-synthase did not label any of the traced structures. These findings provide evidence for opioidergic transmission in thalamo-cortical transduction.